Conflict of Interest in Peer-Reviewed Medical Journals: The World Association of Medical Editors (WAME) Position on a Challenging Problem - Ferris, Lorraine E; Fletcher, Robert H (Journal of Nepal Paediatric Society, 2010)
("This Editorial may appear in other medical and biomedical journals whose editors are members of WAME." Note to WAME Members: This editorial is being offered for publication in WAME member journals at the discretion of their editors. WAME retains copyright.) DOI: 10.3126/jnps.v30i2.3447 J. Nepal Paediatr. Soc. May-August, 2010 Vol 30(2) 73-76